Total Least Squares Method for Robust Source Localization in Sensor Networks Using TDOA Measurements. (4th August 2011) - Weng, Yang; Xiao, Wendong; Xie, Lihua
Abstract : The TDOA-based source localization problem in sensor networks is considered with sensor node location uncertainty. A total least squares (TLSs) algorithm is developed by a linear closed-form solution for this problem, and the uncertainty of the sensor location is formulated as a perturbation. The sensitivity of the TLS solution is also analyzed. Simulation results show its improved performance against the classic least squares approaches.